Impact of bone marrow nucleated cell subfractions on transplant outcomes in patients with acute lymphoblastic leukemia - Nukui, Jun; Tachibana, Takayoshi; Miyazaki, Takuya; Tanaka, Masatsugu; Matsumoto, Kenji; Ishii, Yoshimi; Numata, Ayumi; Nakajima, Yuki; Matsumura, Ayako; Suzuki, Taisei; Izumi, Akihiko; Hirose, Natsuki; et al. (Hematology (Luxembourg), 2024)
Our previous study showed that a high pre-transplant nucleated cell count in the bone marrow is associated with increased non-relapse mortality (NRM) and decreased overall survival (OS) in patients with acute lymphoblastic leukemia (ALL) in remission. In this retrospective multicenter study, we aimed to examine the association between nucleated cell subfractions and transplant outcomes using the same patient cohort as our previous study. This study included patients with ALL who underwent their first allogeneic hematopoietic stem cell transplantation (allo-HSCT) between 2010 and 2022. The patients were stratified into high and low cell group levels to compare transplant outcomes using cutoff values for predicting OS in each subfraction determined using receiver operating curves. In the cohort of 134 patients, the median values for myeloid, erythroid, monocyte, and lymphocyte series were 16,860/µL (468-229,296), 15,584/µL (34-246,992), 1,446/µL (70-25,296), and 4,215/µL (90-33,856), respectively. The univariate analysis showed that the groups with high levels of myeloid cells (≥38,000/µL, n = 48), erythroid cells (≥25,000/µL, n = 45), and monocyte cells (≥4,200/µL, n = 44) were all associated with worse 3-year OS and higher NRM than the low-level groups. These findings were confirmed by using multivariate analysis. The high cell count group showed a higher incidence of NRM associated with acute graft-versus-host disease or immunological disorders. High myeloid, erythroid, and monocytic cell levels in the bone marrow before allo-HSCT may independently increase the risk of NRM and reduce OS.